Оценка ресурса высоковольтных конденсаторов по результатам испытаний на переменном напряжении - Бутко, С.М.; Рудаков, В.В.; Сергеева, Е.Е.; Рудаков, С.В. (Технічна електродинаміка, 2012)
The method of calculation of life time of high-voltage impuls capacitors with a film dielectric on results the tests of sections of capacitors on AC voltage is presented. Correcting dependence of re-calculation of life time is offered.